The leadership of principals and science heads in schools with a Christian philosophy: expectations and realities - Quarmby, Stuart J (Curtin University, 2010)
Prospective Science Heads and prospective Heads of School all have expectations for the nature of the role that they apply for. This research provides prospective Heads of School and prospective Science Heads in schools based on a Christian philosophy with a pool of information on how the realities in these leadership positions differ from the expectations held by other prospective applicants, the expectations of governance (the employers) and the past expectations of incumbents.The research establishes the views of the key decision makers in a school community based on a Christian world-view regarding: 1. Desired outcomes for students: expectations of the school community. 2. The expected leadership characteristics in the role of Principal. 3. The expected leadership characteristics in the role of Head of Science. 4. The differences in expected leadership characteristics between the roles of Principals and Science Heads. 5. The extent to which the actual leadership role differs from that which was expected for successful applicants for these positions. 6. The extent to which the actual leadership role is understood by staff with aspirations for seeking promotion to that role.